2019
DOI: 10.3892/ol.2019.10267
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's sarcoma of the cervix: A case report of an unusual diagnosis in pregnancy treated with surgery, adjuvant VIDE and radiotherapy

Abstract: Ewing's sarcoma of the cervix is a rare entity and presents with considerable challenges in diagnosis and therapy. Herein, we report a case of a cervical Ewing's sarcoma presenting with FIGO stage Ib, diagnosed during the first trimester of the patient's pregnancy. Imaging with CT scans, MRI of her abdomen and PET-CT verified the locoregional extension of the tumor. The diagnosis was confirmed by immunohistochemistry and molecular analysis. Fluorescence in situ hybridization and RT-PCR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The patient remained disease free for 24 months after the treatment. Two cases were described by Kyriazoglou et al and Khosla et al (Khosla et al, 2014;Kyriazoglou et al, 2019). In both instances, the patients (9 weeks of pregnancy and 10 weeks of pregnancy, respectively) presented with a cervical mass of about 8 cm × 7.6 cm and measuring 5 cm in the greatest dimension, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The patient remained disease free for 24 months after the treatment. Two cases were described by Kyriazoglou et al and Khosla et al (Khosla et al, 2014;Kyriazoglou et al, 2019). In both instances, the patients (9 weeks of pregnancy and 10 weeks of pregnancy, respectively) presented with a cervical mass of about 8 cm × 7.6 cm and measuring 5 cm in the greatest dimension, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The tumor fatality rate is extremely high (65–80%) when cured with surgery or radiation therapy alone for local control of the disorder ( Fan et al, 2017 ). During the previous few decades improvement in chemotherapy, surgery, and beam irradiation therapy have ameliorated the prognosis of patients with ES ( Kyriazoglou et al, 2019 ). Tumors of the pelvis have a poorer prognosis when compared with other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment strategies for ES include neoadjuvant chemotherapy, surgery, adjuvant chemotherapy, and radiation therapy. Kyriazoglou et al reported a case of Ewing's sarcoma of the cervix treated with surgery, adjuvant VIDE therapy (Vincristine 1.5 mg/m 2 day 1, Ifosfamide 3 g/m 2 day 1‑3, Doxorubicin 20 mg/m 2 day 1‑3, Etoposide 150 mg/m 2 day 1‑3), and radiotherapy ( Kyriazoglou et al, 2019 ). The patient in this case report is still living at 42 months following the diagnosis of her tumor after primary surgery followed by chemotherapy and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…ESFT of the cervix is rare and, to the best of our knowledge, only 28 cases were reported in the English literature between 1996 and 2020( Ahmad et al, 2017 , Hu et al, 2017 , Murthy et al, 2020 , Kyriazoglou et al, 2019 , Wang et al, 2017 ). We herein present a case of ESFT of the cervix and describe diagnostic and treatment procedures.…”
Section: Introductionmentioning
confidence: 98%